Expansion of the ISWI chromatin remodeler family with new active complexes. (11th August 2017) - Oppikofer, Mariano; Bai, Tianyi; Gan, Yutian; Haley, Benjamin; Liu, Peter; Sandoval, Wendy; Ciferri, Claudio; Cochran, Andrea G
Abstract: ISWI chromatin remodelers mobilize nucleosomes to control DNA accessibility. Complexes isolated to date pair one of six regulatory subunits with one of two highly similar ATPases. However, we find that each endogenously expressed ATPase co‐purifies with every regulatory subunit, substantially increasing the diversity of ISWI complexes, and we additionally identify BAZ2B as a novel, seventh regulatory subunit. Through reconstitution of catalytically active human ISWI complexes, we demonstrate that the new interactions described here are stable and direct. Finally, we profile the nucleosome remodeling functions of the now expanded family of ISWI chromatin remodelers. By revealing the combinatorial nature of ISWI complexes, we provide a basis for better understanding ISWI function in normal settings and disease. Synopsis: This study identifies novel ISWI regulatory subunit‐ATPase pairings in cells and shows that the complexes within the expanded ISWI family exhibit distinct remodeling activities in vitro, suggesting different biological functions. ISWI complex assembly is highly combinatorial and at least fourteen distinct core complexes exist. The protein BAZ2B is a novel ISWI regulatory subunit. Reconstitution in insect cells produces active ISWI complexes with distinct remodeling activities. Abstract : This study identifies novel ISWI regulatory subunit‐ATPase pairings in cells and shows that the complexes within the expanded ISWI family exhibit distinct remodeling activities in vitro, suggesting different biological functions.